Empowering women in agriculture: critical role of gender-intentional investments in Pakistan - Begum, Khadija (Elsevier, 2025)
Despite substantial investments in Pakistan’s irrigated agriculture sector, women’s conditions have seen limited improvement, emphasizing the need for gender-intentional investments. This study aims to provide evidence on the status of women in the marginalized areas of Dera Ismail Khan and Tank to guide more gender-responsive investment decisions that align with gender equality and the Sustainable Development Goals.